Polymer pencil lead graphite for in vivo radiation dosimetry - Siti Nurasiah, M. N.; Khandaker, Mayeen Uddin *; Bradley, D.A. *; Sani, S.F. A.; Almugren, K.S.; Sulieman, Abdelmoneim (Diamond and Related Materials, 2020)
This work explores the use of polymer pencil‑lead graphite (PPLG) as a novel material for passive radiation dosimetry, analysis including state-of-the-art techniques. The versatility of carbon materials in such applications arises in great part from the strong dependence of their physical properties on the ratio of sp2 (graphite-like) to sp3 (diamond-like) bonds. Investigation has been made of key dosimetric properties of commercially available PPLG, specifically the thermoluminescence (TL) glow curve, dose response, energy dependence, effective atomic number, sensitivity and fading. Four different diameter PPLG rods have been studied, their response to photon irradiations being examined. The PPLGs have been found to provide good linear response within the dose range 10 to 200 Gy, sensitivity increasing inversely with PPLG rod diameter. With a standard deviation <3%, all samples showed excellent reproducibility. The fading study was also calculated, the stability of TL signal being examined at room temperatures in dark condition. Vibrational spectra of the irradiated PPLGs were determined using a 532 nm laser Raman spectrometer while bulk resistance, an indirect measure of dosimetry, was studied via electrochemical impedance spectroscopy. The various dose response evaluations reveal the 2B hardness polymer pencil‑lead to possess favourable dosimetric features, suited to passive sensing of radiation for a range of ionizing radiation applications, medical and sterilizational work included.